IMPROVING VOCABULARY USING TIK TOK APPLICATION - Luluk Syifaul Fitriyah; Norma Ita sholichah (English Language Teaching Journal, 2023)
This research is aimed at investigating of improving vocabulary using Tik Tok Application at Mts Mambaul Ulum Gumukmas. The type of this research is classroom action research (CAR). Classroom action research is a study that consists of several stages in one cycle, namely preparing, acting, observing, and reflecting. In collecting data, researchers used three methods, namely observation, interviews, and tests. The result that can be conveyed are: (a)In the preliminary condition, the students' vocabulary ability is still below the minimum completeness criteria value with an average value of 61.19, (b) The application of video tiktok in learning in the classroom is known to have a positive effect on the development of students' vocabulary skills, in the first cycle it is known that after conducting two meetings on the final test it is known that the average score of children has increased to 75.38, and (c) The application of tiktok videos in the second cycle is known to have increased again from 75.38 in the first cycle, in the second cycle it has increased to 81.76, so it can be concluded that the application of tiktok videos has a good influence on the process and results of vocabulary learning. Keywords: Vocabulary, Tik Tok Application, and Classroom Action Research (CAR)